CO- and H2S-adsorbed one-dimensional AlSi structures for gas sensing applications - Hoang Van Ngoc (Royal Society Open Science)
The potential applications of low-dimensional materials continue to inspire significant interest among researchers worldwide. This study investigates the properties of one-dimensional AlSi monolayers, specifically AlSi nanoribbons, and their adsorption behaviour with CO and H2S molecules. The electronic, magnetic and optical properties of these systems are calculated using density functional theory and the Vienna Ab initio Simulation Package. Results indicate that the structures remain relatively planar with negligible buckling heights. All three studied structures exhibit non-zero magnetic moments; notably, CO adsorption enhances the magnetic moment of the pristine AlSi nanoribbon, whereas H2S adsorption reduces it. Adsorption energy calculations reveal that CO exhibits stronger adsorption compared to H2S. Furthermore, a detailed investigation of the optical properties—including the real and imaginary parts of the dielectric function, absorption coefficient and electron–hole density—demonstrates the potential of these structures in nanotechnology applications, particularly for CO and H2S gas sensing.